What Is the Bakery Industry? - Prychyntovska, Vita (My University, 2014)
Small, home-based businesses may be subject to less rigorous requirements that larger businesses. Each region, however, may have unique requirements. Regulations may also vary based on whether the bakery products are for human or animal consumption.
Keywords: bakery industry; bakery; хлібобулочна промисловість; пекарня; хлебобулочная промышленность; кафедра іноземних мов професійного спрямування